The American Manufactory : Art, Labor, and the World of Things in the Early Republic. - Rigal, Laura (Princeton University Press, 1998)
This cultural history of American federalism argues that nation-building cannot be understood apart from the process of industrialization and the making of the working class in the late-eighteenth-century United States. Citing the coincidental rise of federalism and industrialism, Laura Rigal examines the creations and performances of writers, collectors, engineers, inventors, and illustrators who assembled an early national "world of things" at a time when American craftsmen were transformed into wage laborers and production was rationalized, mechanized, and put to new ideological purposes. American federalism emerges here as a culture of self-making, in forms as various as street parades, magazine writing, painting, autobiography, advertisement, natural history collections, and trials and their transcripts